2015
DOI: 10.7324/japs.2015.501103
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Knowledge, Attitude, and Practice on Pharmacogenovigilance in Drug Safety Questionnaire in Medicine and Pharmacy Students: based on Exploratory Factor Analysis

Abstract: Integration of Pharmacogenomics and Pharmacovigilance in the curricula of future healthcare professionals is essential towards individualized medicine and drug safety. Researchers are lacking in Knowledge, attitude and practice regarding pharmacogenovigilance in drug safety among Malaysian future health professionals. This study is to develop and validate a reliable questionnaire for evaluation of knowledge, attitude and practice o f future Doctors and Pharmacists concerning Pharmacogenovigilance in drug safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…While developing the content, we considered the relevancy and suitability of this questionnaire for young adults in Malaysia. Similar to previous studies (Yau et al, 2015a;Chen et al, 2013), the (Revilla et al, 2014). In addition, this type of scale has been reported to be less time consuming as it limits the confusion that usually happens when answering Likertscale questionnaires.…”
Section: Phase Iii: Test-retest Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…While developing the content, we considered the relevancy and suitability of this questionnaire for young adults in Malaysia. Similar to previous studies (Yau et al, 2015a;Chen et al, 2013), the (Revilla et al, 2014). In addition, this type of scale has been reported to be less time consuming as it limits the confusion that usually happens when answering Likertscale questionnaires.…”
Section: Phase Iii: Test-retest Analysissupporting
confidence: 78%
“…For face validation, a total of 15 to 20 subjects were required for this test (Yau et al, 2015b). The subjects had to evaluate the revised questionnaire following content validation.…”
Section: Phase I: Validity Testmentioning
confidence: 99%
“…Previous researches have demonstrated knowledge gap, good attitude and low practice towards PG among current Doctors and Pharmacists (Yau et al, 2015;Bakhouche and Slanař, 2012;Benzeroual et al, 2012;Bernhardt et al, 2012;Bonter et al, 2011;Stanek et al, 2012;Johansen Taber and Press, 2014;Yau et al, 2015b); Moreover, study conducted in Ukraine among Pharmacy students revealed similar results (Filiptsova et al, 2015). However, study carried out in Malaysia, have discovered that current healthcare practitioners have good knowledge, attitude and consider PG to be a relevant field of clinical practice, but with low adoption (Bannur et al, 2014), and other studies have demonstrated healthcare students agree that PG is critical to patient care (Drozda et al, 2013;Gurwitz et al, 2005;McCullough et al, 2011;Moen and Lamba, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…The questionnaire and the informed consent were distributed to the participants via face to face at their respective schools. The questionnaire development, validation and psychometric analysis were explained and published in another article (Yau et al, 2015c).The study was conducted at one of the four randomly selected Malaysia universities. This article reported only the PG part of the pilot the study.…”
Section: Matarials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation